2021
DOI: 10.3389/fphy.2021.647281
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Detector Size and Positioning on Near-Infrared Measurements and Iso-pathlength Point of Turbid Materials

Abstract: Measuring physical phenomena in an experimental system is commonly limited by the detector. When dealing with spatially defined behaviors, the critical parameter is the detector size. In this work, we examine near-infrared (NIR) measurements of turbid media using different size detectors at different positions. We examine cylindrical and semi-infinite scattering samples and measure their intensity distribution. An apparent crossing point between samples with different scatterings was previously discovered and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…This implies that the IPL point allows for the separation of scattering and absorption; changes in absorption do not affect the position of the IPL point, only attenuating its intensity. , Therefore, in order to accurately determine the position of the IPL point, the absorption coefficient must be kept constant, requiring careful sample preparation . It is also important to know the sample diameter because the position of the IPL point is proportional to the optical depth, which is accounted for both by the sample diameter and the distance between the detector and the sample. , In a previous study, it was possible to isolate the absorption coefficient from the light intensity even when the scattering was unknown . This was due to the correction for the Beer–Lambert law with the IPL separation of the scattering from the absorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the IPL point allows for the separation of scattering and absorption; changes in absorption do not affect the position of the IPL point, only attenuating its intensity. , Therefore, in order to accurately determine the position of the IPL point, the absorption coefficient must be kept constant, requiring careful sample preparation . It is also important to know the sample diameter because the position of the IPL point is proportional to the optical depth, which is accounted for both by the sample diameter and the distance between the detector and the sample. , In a previous study, it was possible to isolate the absorption coefficient from the light intensity even when the scattering was unknown . This was due to the correction for the Beer–Lambert law with the IPL separation of the scattering from the absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The DPF is the differential pathlength factor, dependent upon μ a , μ s , and the scattering phase function . Previous research on the IPL point has only been conducted on samples where light experiences multiple scattering events, known as the multiple scattering regime (the measured point is larger than 1/μ s ′ from the light source). ,, For the study of contaminants in drinking water, we consider samples where light scatters only a few times, known as the single or intermediate scattering regime. The scattering in the system is determined by the concentration of insoluble particles, their size, and the geometry of the system. , Higher concentrations of insoluble particles will result in more scattering events .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous publications [14] in 13mm diameter, we found the IPL position at 117 degrees. However, in our recent publication [23], we showed that a factor of 16 increment in detector size, (13mm 2 compared to 0.8mm 2 ) shifts the IPL position by 15 degrees. Moreover, a small change in the distance of the detector from the phantom's surface may explain the additional 3 degrees shift in the IPL position.…”
Section: A Comparison Of Fsps With and Without Spatial Modulationmentioning
confidence: 70%
“…16,20 To address this, adjustments to the sample diameter or the distance between the detector and the sample can be made. 21 Hence, satisfying these conditions is important to ensure a consistent IPL point for each material. Previous research on the IPL point had been conducted on samples where light experiences multiple scattering events, known as the multiple scattering regime (the measured point is larger than 1/μ s ′ from the light source).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the IPL point grants the separation of scattering and absorption; changes in absorption do not affect the position of the IPL point, merely reducing its intensity. , Therefore, precisely determining the position of the IPL point involves careful sample preparation and keeping the absorption coefficient constant. Also, knowing the sample diameter is important because the IPL point position is proportional to the optical path length. , To address this, adjustments to the sample diameter or the distance between the detector and the sample can be made . Hence, satisfying these conditions is important to ensure a consistent IPL point for each material.…”
Section: Introductionmentioning
confidence: 99%